AdipoRon Promotes the Osseointegration of Dental Implants in Mice With Type 2 Diabetes Mellitus - Huang, BoRui; Bi, Wei; Sun, Yang; Li, Ruixue; Wu, Xingwen; Yu, Youcheng (Frontiers in Physiology, 2021)
AdipoRon is an oral active synthetic small molecule with biological functions similar to adiponectin (APN). It is an APN receptor agonist that can improve insulin resistance and glucose intolerance. However, the role of AdipoRon in bone metabolism and related molecular mechanisms remains to be investigated. To explore the effect of AdipoRon on bone absorption and bone integration of type 2 diabetes mellitus (T2DM) mice with implants, we established surgery-induced model of osseointegration of dental implantation in T2DM mice of C57BL/6 db/db and normal mice homologous to diabetic mice. Micro-CT was used to analyze the femurs with the implant in the mice to detect the bone mass, H&E, and tartrate-resistant acid phosphatase (TRAP), and Safranin O-fast green staining was performed to analyze the bone formation and bone resorption. Bone integration-related markers as Rankl, bone morphogenetic protein 2 (BMP2), osteoprotegerin (OPG), osteopontin (OPN), and runt-related transcription factor 2 (Runx2) were also measured using immunohistochemistry. Our results indicated that diabetic mice showed a lower bone mass and decreased the osteoblast differentiation. AdipoRon attenuated diabetes-impaired bone volume (BV)/total volume (TV), trabecular thickness (Tb.Th), trabecular number (Tb.N), trabecular separation (Tb.Sp), and bone integration-related markers variation and promoted bone hyperplasia as well as repressed the osteoclast formation, especially in diabetic mice. AdipoRon may improve the osseointegration of dental implants in mice with T2DM by promoting osteogenesis and inhibiting bone resorption, and AdipoRon may serve as a promising oral strategy to improve the osseointegration ability of patients with diabetes.